2023
DOI: 10.1007/s11356-023-30714-2
|View full text |Cite
|
Sign up to set email alerts
|

Effective triclosan removal by using porous aromatic frameworks in continuous fixed-bed column studies

Ye Li,
Fuxin Gong,
Wu Yang
et al.

Abstract: Triclosan (TCS) has been regarded as an emerging contaminant in aquatic systems, so its e cient removal holds great signi cance. In this study, NPVMo@iPAF-1, with speci c surface area of 665 m 2 /g, prepared by incorporating (NH 4 ) 5 H 6 PV 8 Mo 4 O 40 into porous aromatic frameworks (PAF) was obtained.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…Findings indicated that an increase in the removed bed height at 2, 4, and 6 cm led to a rise in adsorption capacity (q0.5) to 31.99, 50.76, and 62.60 mg/g, respectively. As shown in Figures 10-a the breakthrough curve became gentler, indicating an increase in breakthrough time and saturation time [36]. Therefore, this significantly contributed to extending the lifespan of the column from 1,770 to 5,280 minutes, compared to the lifespan of the fixed-bed column at 870 minutes.…”
Section: Analysis Of Breakthrough Curves Using the Thomas And Yoon-ne...mentioning
confidence: 90%
See 1 more Smart Citation
“…Findings indicated that an increase in the removed bed height at 2, 4, and 6 cm led to a rise in adsorption capacity (q0.5) to 31.99, 50.76, and 62.60 mg/g, respectively. As shown in Figures 10-a the breakthrough curve became gentler, indicating an increase in breakthrough time and saturation time [36]. Therefore, this significantly contributed to extending the lifespan of the column from 1,770 to 5,280 minutes, compared to the lifespan of the fixed-bed column at 870 minutes.…”
Section: Analysis Of Breakthrough Curves Using the Thomas And Yoon-ne...mentioning
confidence: 90%
“…Conversely, this led to a decrease in kYN from 0.0056 to 0.0025 min -1 and an increase in τ from 501.39 to 948.68 minutes for the Yoon-Nelson model. These changes extended the column retention time and resulted in slower saturation of adsorption, attributed to the increase in bed depth, which induced higher axial dispersion and mass transport resistance [35,36]. Breakthrough curve parameters in the pulsed-bed column experiments were calculated and summarized in Table 7.…”
Section: Analysis Of Breakthrough Curves Using the Thomas And Yoon-ne...mentioning
confidence: 99%